Cinnamomum: The New Therapeutic Agents for Inhibition of Bacterial and Fungal Biofilm-Associated Infection - Didehdar, Mojtaba; Chegini, Zahra; Tabaeian, Seidamir Pasha; Razavi, Shabnam; Shariati, Aref (Frontiers in Cellular and Infection Microbiology, 2022)
Due to the potent antibacterial properties of Cinnamomum and its derivatives, particularly cinnamaldehyde, recent studies have used these compounds to inhibit the growth of the most prevalent bacterial and fungal biofilms. By inhibiting flagella protein synthesis and swarming motility, Cinnamomum could suppress bacterial attachment, colonization, and biofilm formation in an early stage. Furthermore, by downregulation of Cyclic di‐guanosine monophosphate (c‐di‐GMP), biofilm-related genes, and quorum sensing, this compound suppresses intercellular adherence and accumulation of bacterial cells in biofilm and inhibits important bacterial virulence factors. In addition, Cinnamomum could lead to preformed biofilm elimination by enhancing membrane permeability and the disruption of membrane integrity. Moreover, this substance suppresses the Candida species adherence to the oral epithelial cells, leading to the cell wall deformities, damage, and leakages of intracellular material that may contribute to the established Candida’s biofilm elimination. Therefore, by inhibiting biofilm maturation and destroying the external structure of biofilm, Cinnamomum could boost antibiotic treatment success in combination therapy. However, Cinnamomum has several disadvantages, such as poor solubility in aqueous solution, instability, and volatility; thus, the use of different drug-delivery systems may resolve these limitations and should be further considered in future investigations. Overall, Cinnamomum could be a promising agent for inhibiting microbial biofilm-associated infection and could be used as a catheter and other medical materials surface coatings to suppress biofilm formation. Nonetheless, further in vitro toxicology analysis and animal experiments are required to confirm the reported molecular antibiofilm effect of Cinnamomum and its derivative components against microbial biofilm.